Juridical Review On The Policy For The Utilization Of Green Open Space In Semarang City - Agus Widodo; Widayanti (International Journal of Educational Research & Social Sciences, 2022)
Green open space has socio-economic and environmental functions, so green open space must become a comfortable place for the community. Urban green space is an integral part of the structure of the city. The primary function of the town is as an ecological buffer and as an open space area to enhance and support the value of environmental and cultural quality. Mark. The existence of urban green open space is necessary to control and maintain the integrity and quality of the environment. The method used is descriptive in the form of normative juridical. The data used are primary and secondary, and the data collection used is library research. The Semarang city government is expected to become an actor in implementing regional spatial planning policies to provide green open space. The absence of green open space in urban areas will cause environmental problems. One of the problems that arise is the increasing air pollution caused by the lack of ecological balance in urban areas. Another harmful effect of small green spaces is that Without trees to keep the room more excellent, the people's health in the area is compromised.